2004
DOI: 10.1023/b:bile.0000025888.93564.a0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mycelial growth and polysaccharide production in Ganoderma lucidum (the Chinese medicinal fungus, `Lingzhi') by the addition of ethanol

Abstract: Methanol, ethanol, 1-propanol and 2-propanol, at 1.5% (v/v), enhanced the growth and polysaccharide production of Ganoderma lucidum. Ethanol was the most effective at 1.5% (v/v) for increasing the biomass production, however, the maximal polysaccharide concentration was produced with 2% (v/v) ethanol in the medium. There was no new polysaccharide component produced by the addition of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 7 publications
0
22
1
Order By: Relevance
“…Combination of statistical techniques offers a strategy for studying many variables including nutrient requirements and culture conditions in fewer experimental runs, leading this method to be widely used to screen multiple variables of fermentation processes. Literature reviews of many studies on nutritional requirements for Ganoderma fungus has shown that a carbon source of brown sugar, a nitrogen source of skim milk, plant olive oil, CaCO 3 (Chang et al, 2006), MgSO 4 ·7H 2 O, K 2 HPO 4 , KH 2 PO 4 (Hsieh et al, 2006) and ethanol (Yang et al, 2004) effectively promoted biomass and EPS. Moreover, cheese whey (Lee et al, 2003), brown sugar, skim milk (Chang et al, 2006) and molasses, increased production because these components contain various vitamins and other nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of statistical techniques offers a strategy for studying many variables including nutrient requirements and culture conditions in fewer experimental runs, leading this method to be widely used to screen multiple variables of fermentation processes. Literature reviews of many studies on nutritional requirements for Ganoderma fungus has shown that a carbon source of brown sugar, a nitrogen source of skim milk, plant olive oil, CaCO 3 (Chang et al, 2006), MgSO 4 ·7H 2 O, K 2 HPO 4 , KH 2 PO 4 (Hsieh et al, 2006) and ethanol (Yang et al, 2004) effectively promoted biomass and EPS. Moreover, cheese whey (Lee et al, 2003), brown sugar, skim milk (Chang et al, 2006) and molasses, increased production because these components contain various vitamins and other nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, technique of submerged fermentation was interested from biopharmaceutical industry, because it has short time cultivation, easy to control condition for contaminated protection and obtain best product in quality and quantity (Narkprasom et al, 2012). The production yield of G. tsugae cultured using submerged fermentation is affected by many parameters, such as agitation, aeration, temperature, pH, dissolved oxygen, nutrient composition and fermentation time (Chang et al, 2006;Hsieh et al, 2006;Yang et al, 2004;Lee et al, 2003) and these parameters are critical for the production of G. tsugae. The optimization method for many parameters in fermentation process of G. tsugae has attracted significant interest from pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Haq et al [22] had reported that alcohols addition could increase the permeability of cell membrane in Aspergillus niger culture. Yung et al [15] also found that ethanol addition could enhance mycelial biomass and EPS productions in Ganoderma lucidum culture. However, in this study, all the alcohols expressed negative effect on cell growth and EPS production in G. umbellate submerged culture.…”
Section: Alcohols Additionmentioning
confidence: 95%
“…In this study, in order to search for a proper additive to accelerate mycelia biomass and EPS productions in G. umbellata culture, the additives with stimulatory effects [14][15][16][17][18][19], including organic acids, alcohols, vegetable oils, surfactants and polymers were employed to test their stimulatory effects on both mycelia growth and EPS production in G. umbellata culture. Meanwhile, the effective additive for mycelia growth and EPS production was selected and the cultivation conditions were investigated and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that microbial polysaccharides, especially polysaccharides from medicinal fungi, have a very strong biological activity, such as polysaccharides of G. frondosa (Nanba, 1995;Hsieh et al, 2008;Huang and Chen, 2009), polysaccharides of G. lucidum (Yang et al, 2004;Liu and Zhang, 2007), and polysaccharides of Phellinus igniarius (PL) (Zou et al, 2006). Therefore, it has been a concern widely to most researchers on how to get the maximum amount of polysaccharides from medicinal fungi (Yang and Liau, 1998;Zhong, 2002, 2003).…”
Section: Ideas Of Research On Microbial Fermentation and Transformatimentioning
confidence: 99%